Peran BAZNAS Kabupaten Pasaman Barat dalam Meningkatkan Ekonomi Masyarakat - Rohida Rohida (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the persistent levels of poverty and economic vulnerability among communities in West Pasaman Regency, despite the region’s considerable economic potential in agriculture, trade, and micro-enterprise sectors. In this context, the National Zakat Agency (BAZNAS) of West Pasaman plays a strategic role as a zakat management institution that not only distributes consumptive assistance but also develops productive zakat programs aimed at strengthening the economic independence of mustahik. Programs such as business capital support, provision of production tools, entrepreneurship training, and ongoing business mentoring are key instruments examined in this study. Using a qualitative descriptive approach, the research was conducted at the BAZNAS office and several districts where mustahik beneficiaries reside. The findings indicate that productive zakat programs significantly contribute to improving community livelihoods by increasing business capital, enhancing turnover, creating job opportunities, and reducing dependence on consumptive aid. The impacts include increased income, better fulfillment of basic needs, and growing business independence, although the level of success varies among beneficiaries. The study also identifies challenges such as limited funds and human resources, low awareness among some muzakki, and difficulties in monitoring businesses across wide areas. Overall, BAZNAS plays an important role but requires strengthened governance and expanded program outreach for optimal impact.